Making Preparation Practical: Reducing Aspiring Administrator Time to Competence Through Five Types of Leaderly Thinking (Journal of School Administration Research and Development, 2018)
California faces an increasing shortage of well-prepared, competent school leaders. These future instructional leaders will be required to play critical roles to assure the success of the schools they will lead. San Diego State University, in collaboration with three partner school districts in the region, developed the five types of leaderly thinking model to represent a leader’s integration and application of the broad and disparate knowledge required to successfully lead a school. The model was designed to scaffold the design of administrative credential courses that accurately reflect the realities of school leadership. In doing so, the partners intend to provide candidates with experiences that reflect a leader’s true work and, through the authentic, practice-based learning experience, reduce the new administrator’s time to competence. This article presents the five types of thinking and highlights the implementation of this model into the preparation program. Additionally, it provides ideas to guide the model’s application in school district-based professional development applications.